Age and rate of weathering determined using uranium-series isotopes: Testing various approaches. (1st February 2019) - Dosseto, Anthony; Menozzi, Davide; Kinsley, Leslie P.J.
Abstract: The development of weathering profiles shapes Earth's surface and regulates its climate via chemical weathering. Hence, it is essential to be able to determine the age of weathering profiles and quantify how fast they form. Uranium-series isotopes allow for such quantification. However, isotope compositions are generally measured in bulk regolith, which represents a complex mixture of mineral and organic phases of different origins that can impact the reliability of the information derived from U-series isotopes. Thus, in this study, we assess whether sequential extraction and mineral separation could provide more reliable estimates of weathering ages and rates. We focus on a granitic profile developed under temperate climate in southeastern Australia, a tectonically quiescent environment. Regolith production rates have been independently estimated in the region using cosmogenic isotopes. As expected, the mineralogy and geochemistry of the bulk regolith show that biotite and feldspar are the main phases lost during weathering, progressively replaced by clay minerals. There is no evidence for significant input of element from external sources, such as via aerosol deposition. While sequential extraction does not seem to affect major mineral phases and element concentrations, it is suspected of producing artificial radioactive disequilibrium. Biotite separates show very large accumulation of U and Th, which increases with decreasing depth. Regolith production rates and mineral dissolution rates calculated with weathering rates estimated using the bulk saprolite and quartz separate compositions yield values comparable to independent estimates. Conversely, weathering ages derived from the compositions of saprolite leached experimentally or biotite separates underestimate regolith production rates and mineral dissolution rates. Thus, sequential extraction or biotite separation are not recommended methods to derive reliable rates of regolith production and mineral dissolution. Despite the potential complexity of the composition of bulk regolith, the use of regolith without any pre-treatment seems to yield satisfying estimates of regolith production and mineral dissolution rates. The composition of quartz separates yields rates similar to those derived from bulk compositions. This provides an alternative method, potentially allowing reliable results to be obtained from a single mineral phase rather than a complex mixture of weathering products.